Outdoor Laboratories in Social Studies Learning: A Systematic Review and Pedagogical Implications: Laboratorium Luar Ruang dalam Pembelajaran Ilmu Sosial: Tinjuan Sistematis dan Implikasi Pedagogis - gunawan; Fredy Hermanto; Amrin Ma’ruf; Latif Hendro Wibowo (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Social science faces the challenge of bridging the gap between theoretical concepts and the dynamics of social reality. Conventional learning models tend to limit learning experiences, making it difficult to understand the complexity of an ever-changing social reality. This study aims to identify forms of outdoor laboratories and learning models that can support the learning process in the social sciences. The research method employed a literature review, with literature searches conducted through Publish or Perish, Consensus, Google Scholar, Gate, and Scopus using the keywords: